90-day nose-only inhalation toxicity study of 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) in Sprague-Dawley rats. (February 2022) - Hu, Shu-Chieh; Min, Seonggi; Kang, Hyun-Ki; Yang, Dong-Jin; Basavarajappa, Mallikarjuna; Lewis, Sherry M.; Davis, Kelly J.; Patton, Ralph E.; Bryant, Matthew S.; Sepehr, Estatira; Trbojevich, Raul; Pearce, Mason G.; et al.
Abstract: 4-(Methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK) is one of the key tobacco-specific nitrosamines that plays an important role in human lung carcinogenesis. Repeated dose inhalation toxicity data on NNK, particularly relevant to cigarette smoking, however, is surprisingly limited. Hence, there is a lack of direct information available on the carcinogenic and potential non-carcinogenic effects of NNK via inhalational route exposure. In the present study, the subchronic inhalation toxicity of NNK was evaluated in Sprague Dawley rats. Both sexes (9–10 weeks age; 23 rats/sex/group) were exposed by nose-only inhalation to air, vehicle control (75% propylene glycol), or 0.2, 0.8, 3.2, or 7.8 mg/kg body weight (BW)/day of NNK (NNK aerosol concentrations: 0, 0, 0.0066, 0.026, 0.11, or 0.26 mg/L air) for 1 h/day for 90 consecutive days. Toxicity was evaluated by assessing body weights; food consumption; clinical pathology; histopathology; organ weights; blood, urine, and tissue levels of NNK, its major metabolite 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanol (NNAL), and their glucuronides (reported as total NNK, tNNK, and total NNAL, tNNAL, respectively); tissue levels of the DNA adduct O 6 -methylguanine; blood and bone marrow micronucleus (MN) frequency; and bone marrow DNA strand breaks (comet assay). The results showed that NNK exposure caused multiple significant adverse effects, with the most sensitive endpoint being non-neoplastic lesions in the nose. Although the genotoxic biomarker O 6 -methylguanine was detected, genotoxicity from NNK exposure was negative in the MN and comet assays. The Lowest-Observed-Adverse-Effect-Level (LOAEL) was 0.8 mg/kg BW/day or 0.026 mg/L air of NNK for 1 h/day for both sexes. The No-Observed-Adverse-Effect-Level (NOAEL) was 0.2 mg/kg BW/day or 0.0066 mg/L air of NNK for 1 h/day for both sexes. The results of this study provide new information relevant to assessing the human exposure hazard of NNK.